Inter-regional migration modelling - a review and assessment - John Stillwell (European Regional Science Association (ERSA), 2005)
Population migration involves the relocation of individuals, households or moving groups between geographical locations. Aggregate spatial patterns of movement reflect complex combinations of motivation that influence migration behaviour and determine destination choice. Consequently there is a huge literature on modelling different types of migration at various spatial scales. This paper, which originates from a study for EUROSTAT to find a generally applicable migration model, endeavours to review the state of the art by exploiting the distinction between explanatory and projection models. Whilst the review inevitably lacks comprehensiveness, it demonstrates the difference between mathematical and statistical approaches, highlights a recent two-stage model developed for use in a policy context in the UK, and contrasts these methods with models developed in the context of multi-state demography and used for migration projection in the European Union.
Keywords: 330